Stercoraceous perforation, rare but potentially fatal cause: case report - Durán Gutiérrez, Carlos; Alvarez Rojas, Andres Felipe; Rios Muñoz, Braulio; Diez Martínez Tana, Veronica (International Journal of Research in Medical Sciences, 2023)
Stercoraceous perforation is an infrequent pathology but with high mortality rates, it is increasingly recognized as a consequence of chronic constipation, it occurs in elderly people, the diagnosis is a surgical challenge, sudden abdominal pain is the initial symptom associated with signs of peritoneal irritation and the diagnostic study of choice is tomography, the treatment of choice is early surgery, the prognosis is related to the patient's comorbidities. We present the clinical case and review of the subject of a 72-year-old woman who presented stercoraceous perforation secondary to chronic constipation, emergency surgery was performed with resection of the affected bowel, colostomy and Hartmann's pouch with favorable short-term results.